Teaching Geography in Secondary School: Teachers Perceptions and Experiences (The Geographic Base, 2019)
Geography has the feature of being a science by examining the relationship of human and nature. Geography occupies very important role in school education. In secondary level education within Nepal there is a provision of selection of geography as an optional subject. This paper examines the perception and experiences about geography as an academic discipline from the teacher of secondary levels. Qualitative research method is used in this study and the semi structured interview method is applied. A semi structured interview guideline is applied for the participant in this study. Data are categorized into seven different groups and the analysis is carried out through the interpretations. The Research findings are discussed in relation to the theme and some recommendations have been given. This article provides useful information on the topic of perceptions and experiences of geography teachers on geography teaching in secondary school of Nepal.